NOWHERE FAST? SHORTCUTS TO JUDGMENT IN RECENT ITALIAN PROCEDURAL LEGISLATION - Michele Angelo Lupoi (Revista Eletrônica de Direito Processual, 2017)
The text deals with the measures adopted in Italian law, which created new procedural rules, in order to allow greater agility in the rendering of decisions on merit. This paper deals with the new rules regarding the granting of anticipatory provisional measures, as well as summary procedures for simpler cases, the procedural switch to summary proceedings, and the new filter for appeals.